Permanently temporary. Street experiments in the Torino Mobility Lab project - Staricco, Luca; Verlinghieri, Ersilia; Vitale Brovarone, Elisabetta (TeMA - Journal of Land Use, Mobility and Environment, 2024)
Street experiments introduce changes in the use, regulation or form of streets with the aim of triggering systemic shifts in urban mobility from motorized traffic to active travel and more livable public space. Generally intended to be temporary at implementation, street experiments may be repeated over time or even become permanent, depending on their success. This paper analyses four experimental road reallocation interventions that were implemented in August/December 2020 in the Italian city of Turin, as part of the Torino Mobility Lab project. These pedestrianizations were implemented in a temporary, experimental and low-cost way for four months, during which a monitoring activity was launched in order 1) to measure the use and the perception of the value of these temporary pedestrianizations in order to decide whether or not to make them permanent, and 2) to collect data on the ways they were used, as well as suggestions from their users for the design of the permanent versions of those that would have been confirmed. The paper analyses this monitoring/evaluation process and identifies some barriers and factors that can complicate and slow down the transition from temporary to permanent street reallocation.